2016
DOI: 10.1177/0022429416637596
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Outside In

Abstract: Through the lens of hospitality, we explored the meanings that members constructed about their experiences within a blended formal/informal college music ensemble. The focus in this ensemble was not on competition and musical excellence but on independent musicianship and praxis. The bandleader had his roots in tradition but his heart in socially relevant pedagogy and favored a less autocratic teaching and learning style. The makeup of the ensemble also included students from both formal and informal backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Finally, participants in the current study indicated that they primarily consult colleagues, students, and YouTube when searching for vernacular ideas and ways to improve their teaching. Given that teachers reported conferring with students in discussions about music that was important to them, participants appeared to display the interconnected tenets of collaborative learning, out-of-school connections, and culturally relevant pedagogy that West and Cremata (2016) and Mercado (2019) outlined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, participants in the current study indicated that they primarily consult colleagues, students, and YouTube when searching for vernacular ideas and ways to improve their teaching. Given that teachers reported conferring with students in discussions about music that was important to them, participants appeared to display the interconnected tenets of collaborative learning, out-of-school connections, and culturally relevant pedagogy that West and Cremata (2016) and Mercado (2019) outlined.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this process has involved reconciling tensions between formalized Western classical traditions and the informal skills that individuals display in vernacular and popular music-making contexts (e.g., structure and exploration, teacher-led and student-led, pre-composed and spontaneously composed) (Blackwell et al, 2022; Davis & Blair, 2011; Hamilton & Vannatta-Hall, 2020; Isbell, 2016). Such notions could support a more thorough examination of vernacular genres and could provide a more equitable philosophical balance between utilitarian and aesthetic viewpoints (Hess, 2020; Jenkins, 2011; West & Cremata, 2016). Providing an array of ensemble choices in schools might be one way to meet the breadth of student motivation (Rolandson, 2020; Weinstein & Haning, 2022) for participating in school music offerings.…”
Section: Introductionmentioning
confidence: 99%
“…Because the choir does not have a formal performance as the primary goal, this broader approach with a music education focus seems a good use of the time, energy, and resources for the director/teacher, music education students, and the university music unit. West and Cremata (2016) suggested that the addition of informality to the music rehearsal, including instances that function as hospitality, results in new additional types of learning and potential increases in group cohesiveness. Aspects of this approach could be added to some performance-focused groups of varying ages in ways that do not detract from the rehearsal time needed for performance readiness as long as personnel and facilities were available.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, researchers have found that informal music groups created diverse musical experiences (Tobias, 2015; West & Cremata, 2016). One high school student appreciated her song writing and technology class more than her performance-oriented ensembles.…”
Section: Perceived Dissonancementioning
confidence: 99%